2013
DOI: 10.2306/scienceasia1513-1874.2013.39.610
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anticancer activities of (−)-zeylenol from stems of Uvaria grandiflora

Abstract: Uvaria grandiflora has stimulated rigorous phytochemical investigation aimed at determining chemical structures and biological activities. In recent years, many polyoxygenated cyclohexenes have been isolated from this genus. This study reports that zeylenol isolated from the stems of U. grandiflora possess potential anti-inflammatory, anticancer, and caspase-3 activities. The structure of this compound was elucidated from spectroscopic analysis, particularly 2D NMR techniques. The anti-inflammatory effect and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Thus, this study provides some scientific evidence of the usage of these three species in traditional anti-cancer and anti-inflammatory regimens. Seangphakdee et al ( 2013 ) reported similar anti-inflammatory activity for poly-oxygenated cyclohexane zeylenol (35) (Figure 1 ) isolated from Uvaria grandiflora . Anti-inflammatory activity of zeylenol (35) was evaluated on rats using ear edema assay.…”
Section: Anti-inflammatory Activitymentioning
confidence: 75%
“…Thus, this study provides some scientific evidence of the usage of these three species in traditional anti-cancer and anti-inflammatory regimens. Seangphakdee et al ( 2013 ) reported similar anti-inflammatory activity for poly-oxygenated cyclohexane zeylenol (35) (Figure 1 ) isolated from Uvaria grandiflora . Anti-inflammatory activity of zeylenol (35) was evaluated on rats using ear edema assay.…”
Section: Anti-inflammatory Activitymentioning
confidence: 75%
“…The antimicrobial activity against tested microbes including Staphylococcus aureus (ATCC29213), Escherichia coli (ATCC25922), and Candida albicans (ATCC 10231) at 10 µg/ml concentration revealed that all the compounds screened did not show inhibitory activity (for information detail; see Table S4). According to literature reports, the crude extracts and pure compounds isolated from various parts of U. grandiflora were examined for several biological activities such as cytotoxic, anti-inflammatory, antioxidant, and antimicrobial activities [6][7][8][9][20][21][22]. To the best our search from SciFinder database, compounds 1-6 have never been investigated for their antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…We were unable to characterize the other peaks because of impurity and then insufficient amount and further work need to be done with this plant. Zeylenol is a known constituent of U. grandiflora (Seangphakdee et al, 2013) whereas ferrudiol is reported for the first time from this plant. We tested zeylenol and ferrudiol for cytotoxicity against MRC-5, which were both non-toxic.…”
Section: Accepted Manuscriptmentioning
confidence: 99%